If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(12w-3)=6w
We move all terms to the left:
2(12w-3)-(6w)=0
We add all the numbers together, and all the variables
-6w+2(12w-3)=0
We multiply parentheses
-6w+24w-6=0
We add all the numbers together, and all the variables
18w-6=0
We move all terms containing w to the left, all other terms to the right
18w=6
w=6/18
w=1/3
| 9x-32=12+76 | | (25n^2-55n+24)=0 | | 8x-x-115=95 | | (6+z/10)=12 | | -5.5r+0.56=-1.64 | | 0=3x^2+6x-45 | | 1/8×7=x | | -57=4x+4x+7 | | 78x-x=87-x | | 17=x+4(x+3) | | 10(x)=-8x+100 | | 3t−18=-12-3t | | 8x^2+13=277 | | 6-7x=7x-9x-4 | | (5n^2-11n+24)=0 | | (n+3/8)=4 | | 21j^2+14j-56=0 | | x/2+3/8=3/4 | | 6x-60+180=180 | | -5+m/8=-4 | | 268=36-u | | 4x-7x-5=4 | | 7=(x+2)/4 | | x^2-4x+2=2-x | | -1+6(7x+6)=4x-4+7 | | 3(z+11)^2-40=440 | | 4-(9x+6)=-x | | 11h^2-7h-4=0 | | -116+6x-15x=217 | | 1(1)-10m-87=-9 | | 10x+2=10x-5 | | 2-x=x^2-4x+2 |